KOMPETENSI DAN PROFESIONALISME GURU PENGARUHNYA TERHADAP KUALITAS PESERTA DIDIK PADA SEKOLAH LANJUTAN TINGKAT ATAS DI KECAMATAN SUNGAI TABUK KABUPATEN BANJAR - Muhammad Fitri Ramadhan; Basuki Basuki; Maskur Maskur (Universitas Islam Kalimantan Muhammad Arsyad Al Banjari, 2020)
Teacher competency in mastering competency standards and basic subjects taught, reflected in the personality of the teacher. This study aims to describe the teacher's competency, teacher professionalism, description of the quality of students and the influence of teacher competency on the quality of students, teacher professionalism on the quality of students and the influence of teacher competency and professionalism on the quality of students in upper tier schools in Sungai Tabuk Subdistrict Banjar Regency, South Kalimantan Province. This type of research is quantitative research that is processed by statistical methods. The sampling technique in this study uses census method techniques or saturated sampling or often called total sampling of 92 students. The results showed that the average score for the teacher competency variable (X1) was 4.46, indicating that the teacher's competence was quite good. Professionalism Teachers with an average score of question items range from 4.30 to 4.51 which indicates that teacher professionalism is good. In the overall analysis of variable items (Y), namely the quality of students with an average score of question items ranging from 3.86 to 4.43, this indicates that the quality of students is good enough. The results of regression analysis Partial t test between teacher competency (X1) on the quality of students (Y) yields the value of the regression coefficient (B) 0.333 and the probability value (p) 0.00 <0.05 thus partially it can be said that there are pengauuh significant between teacher competency towards the quality of students, while the value of R Square (r²) = 0.455 which means that the variation (change) in the quality of students' learning can be influenced by teacher professionalism 0.577% said there is a significant influence between teacher professionalism on the quality of students.